Leap-frogging the urban-poor to a high income economy: a case study from a developing country / Mahendhiran Nair & Santha Vaithilingam. - Nair, Mahendhiran; Vaithilingam, Santha (Universiti Teknologi Mara Selangor, 2013)
Urban-poverty is a major concern for policy-makers in the developing world. If measures are not taken to address urban-poverty, it will result in growing social problems, which can lead to economic and political instability. It is widely recognized that ICT is a leap-frogging technology that can close the knowledge-divide and income gap between the ‘haves’ and ‘have-nots’. In this study, we examine if ICT diffusion can improve the income level of urban-poor communities in Malaysia. Three types of ICT were considered in this study, namely mobile phones, computers and internet. The study was conducted using survey data for 434 respondents from selected urban-poor communities in the Klang Valley region in Malaysia. The empirical analysis showed that all three ICTs enhanced the income level of this marginalised community. This provides evidence that ICT diffusion strategies should be an integral part of national development plans to address urban-poverty in developing countries.